Ileitis in Adult Multisystem Inflammatory Syndrome: A Case Report - Michelle Forson; Michael Aljadah; Lindsay Hammons; Alexandra Harrington; Poonam Beniwal-Patel; Anna Johnson; Eric Krumpelbeck; Joshua Field; Erin Strong; Joshua Pearl; Adrian Umpierrez; Jayshil J. Patel (Annals of Internal Medicine: Clinical Cases)
Multisystem inflammatory syndrome (MIS) can manifest with nonspecific gastrointestinal symptoms, fever, shock, and cardiovascular dysfunction. Compared with children, MIS in adults (MIS-A) is rare. We present a definitive case of MIS-A (based on the Brighton criteria) in a young adult with fever, erythematous rash, and prominent gastrointestinal (ileitis) features, elevated inflammatory markers with evidence of cardiac involvement, and renal injury 4 weeks after confirmed SARS-CoV-2 infection. We highlight the histopathologic features from an ileal biopsy, which demonstrated reactive lymphocytic infiltrates. To our knowledge, this is the first report describing intestinal histopathologic findings in MIS-A.